Development of a Virtual Reality Assistive Tool for Individual with Autism Spectrum Disorder - Ting, Sing Hong (Universiti Malaysia Sarawak (UNIMAS), 2019)
A recent report indicates that 1 in 59 children worldwide has autism spectrum disorder (ASD). Virtual Reality (VR) assistive tool technologies are becoming conventional therapies for strengthening of behaviour and learning of the individual with ASD. The main issues with the initial VR assistive tool technologies and research is that the initial VR technologies have been unable to sustain engagement in social interaction with ASD patient. This research aim for develop a VR assistive tool for ASD patient and analyse the effect of the VR tool toward Heart Rate Variability (HRV) of the ASD patient. Several responsive elements related to ASD is included in the process of designing the VR assistive tool. Three sets of HRV data of the normal developed children is collected and analysed. The HRV data effectively represent the psychological effect of the VR assistive tool toward the children. Keywords: Autism Spectrum Disorder (ASD), Virtual Reality (VR), assistive tool, social interaction.